Gaya Kepemimpinan Kepala Madrasah Tsanawiyah Negeri 6 Kediri - Mohamad Ikhwanul Kirom; Suko Susilo (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2019)
The Head of Madrasa in the Education Unit is a leader. He has two positions: formal leader and school manager. In carrying out their duties, each madrasa head uses different strategies and methods according to his character, known as the leadership style. This research is a type of qualitative research with a descriptive-analytical approach. The sampling technique used is purposive sampling. So the source of data in this study is the headmaster of madrasas, educators, education staff, students, and documents related to the leadership style of the headmaster. The data collection techniques that researchers use in this thesis are observation, interviews and documentation. Data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions. Indications for obtaining maximum results are observations about madrasah head decision making, madrasah head interaction models, madrasah head motivation, orientation/leadership behaviour of madrasas. The results show that, First, the leadership style of the head of MTs Negeri 6 Kediri is situational or combines democratic, authoritarian, laissez-faire but more dominant democracy. Secondly, this madrasa has indeed achieved many achievements at the district, provincial and national levels.